ANALISIS PERSEDIAAN BAHAN BAKU PASIR PADA PRODUK BETON MENGGUNAKAN METODE EOQ DAN POQ DI PT XYZ - Sopadi, Sopadi; Tarman, Tarman; Haris, sandi Yudha (Jurnal Intent: Jurnal Industri dan Teknologi Terpadu, 2024)
Ordering raw materials optimally can provide benefits for the company. PT. XYZ places an order for sand 12 (twelve) times in 1 (one) period which causes it to be ineffective and inefficient. Therefore, it is necessary to have a method that is able to control the total cost of raw material inventory in order to ensure a smooth production process. The EOQ (Economic Order Quantity) method is used to identify orders to minimize the total cost of holding inventory, purchase raw materials with each purchase with a minimum cost, and orders that minimize total inventory costs. Thus the EOQ (Economic Order Quantity) method can save the cost of raw material inventory which is able to make a company profitable by applying this method. The results of this study indicate that the EOQ (Economic Order Quantity) method can save raw material inventory costs compared to traditional methods (policy firms). The savings in the cost of raw materials for sand in the EOQ (Economic Order Quantity) method were Rp.8.394.400.